BS EN IEC 61755-3-2. Fibre optic interconnecting devices and passive components. Connector optical interfaces. Part 3-2. Connector parameters of dispersion unshifted single-mode physically contacting fibres. angled 2, 5 mm and 1, 25 mm diameter cylindrical full zirconia ferrules (1st June 2023) - British Standards Institution,
No abstract available